THE IMPACT OF CULTURAL DIMENSIONS IN QUALITATIVE CHARACTERISTICS OF ACCOUNTING INFORMATION: AN APPLIED STUDY OF A SAMPLE OF IRAQI AND INTERNATIONAL BANKS - Ahmed Jasim Hameed; Saeb Salim Mohammed (Scholar Express Journals, 2023)
The research aims to show the impact of cultural dimensions in qualitative characteristics of accounting information for Iraqi and international banks. The research community includes 15 countries (Iraq, Kuwait, Qatar, Saudi Arabia, United Arab Emirates, Jordan, Egypt, Australia, Belgium, Portugal, Bulgaria, Italy, Poland, Croatia, France) each country selected 3 banks. Independent variable was measured through 6 dimensions that identified by Hofstede. While the variable of the qualitative characteristics of accounting information was measured by proxy of the fundamental qualitative characteristics which are relevance and faithful representation. The research concluded that there is a significant effect of some dimensions (Power Distance-PD, Uncertainty Avoidance-UA) on faithful representation as one of the qualitative characteristics of the accounting information. In addition, power distance was the highest in Iraq, it reached 97 percent which indicates that the level of inequality in society. Also, individualism dimension was highest thing in Australia and Poland, where it reached 90 percent, that show the sovereignty of the laws in these countries
Keywords: cultural dimensions; qualitative characteristics of accounting information